2009
DOI: 10.1158/1541-7786.mcr-08-0200
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-7 Regulates EpCAM-Mediated Functions in Tumor Progression

Abstract: EpCAM has been described as a therapeutically relevant tumor marker. We noted an interaction between EpCAM and the tight junction protein claudin-7 and here explored the nature of this interaction and its effect on EpCAM-mediated functions. The interaction between EpCAM and claudin-7 was defined in HEK293 cells transfected with rat claudin-7 and EpCAM cDNA. Deletions of the epidermal growth factor -like and the thyroglobin repeat domains of EpCAM or the cytoplasmic domain of EpCAM or claudin-7 did not prevent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 54 publications
3
82
1
4
Order By: Relevance
“…The origin of NETs is still debated, but the expression of this carcinoma-associated antigen adds evidence to an epithelial origin rather than being derived from the neural crest as was once originally thought (10,19). EpCAM upregulates c-myc and cyclins, promoting cell cycling and enhancing proliferation (20)(21)(22)(23)(24). Anti-EpCAM therapy has been trialed in metastatic breast cancer, colorectal cancer, and in malignant ascites (25)(26)(27)(28)(29)(30) and EpCAM expression in NETs presents an opportunity for EpCAM directed therapy (9).…”
Section: Discussionmentioning
confidence: 99%
“…The origin of NETs is still debated, but the expression of this carcinoma-associated antigen adds evidence to an epithelial origin rather than being derived from the neural crest as was once originally thought (10,19). EpCAM upregulates c-myc and cyclins, promoting cell cycling and enhancing proliferation (20)(21)(22)(23)(24). Anti-EpCAM therapy has been trialed in metastatic breast cancer, colorectal cancer, and in malignant ascites (25)(26)(27)(28)(29)(30) and EpCAM expression in NETs presents an opportunity for EpCAM directed therapy (9).…”
Section: Discussionmentioning
confidence: 99%
“…Although the direct interaction of EpCAM with claudin-7 has not been formally demonstrated, the relative paucity of other proteins in preparative anti-EpCAM immunoprecipitates from Caco-2 cells suggests that this is the case (12,38). Previous studies have demonstrated that EpCAMclaudin-7 interactions are strongly influenced by amino acid substitutions at 2 positions within the EpCAM transmembrane domain (39). We have confirmed these results (12) but currently have no insights into mechanisms that might link N-terminal cleavage of EpCAM to conformational changes in the EpCAM transmem- Figure 7.…”
Section: Methodsmentioning
confidence: 99%
“…1-4 Although EpCAM can be detected on the basolateral membrane of various normal epithelial tissues, including colon, small intestine, and hepatoblasts, 5 , 6 it is believed to be less accessible to traditional antibody constructs due to sequestration within tight cellular junctions. 7 , 8 The univalent EpCAM antibodies edrecolomab and adecatumumab have shown modest single-agent activity in the treatment of colon, prostate, and breast cancer. 9-11 …”
Section: Introductionmentioning
confidence: 99%